The Essence of the Curriculum - Ruslan; Nurhidayah Da’te; Andi Fitriani Djollong; Rahmaniah; Abdul Assam (Universitas Muhammadiyah Palu, 2025)
The curriculum is the heart of the education system which has a function as a frame of reference in organizing the learning process. In essence, a curriculum is not just a written document containing a list of subjects, but a comprehensive design that includes the entire learning experience planned and guided by an educational institution. The curriculum is dynamic because it is easily adapted to circumstances and adaptive to the development of the times, reflecting the philosophical, sociological, psychological, and pedagogical values embraced in the education system of a country. As a tool to achieve educational goals, the curriculum contains four main interrelated components: objectives, material or content, learning strategies or methods, and evaluation. The objectives of the curriculum are derived from the objectives of national education which reflect the aspirations of the community. Curriculum materials are selected and designed to achieve these goals. Learning strategies determine the approaches, methods, and techniques used in implementing the curriculum. As for evaluation, it serves to measure the success rate of achieving goals and provide feedback for curriculum improvement. In terms of implementation, the curriculum has three forms: the written curriculum (intended curriculum), the implemented curriculum (implemented curriculum), and the experienced curriculum (experienced curriculum). The gap between these three forms of curriculum is often a challenge in achieving educational effectiveness. Therefore, curriculum development needs to be carried out systematically, scientifically, and involving various stakeholders to ensure the relevance, sustainability, and significance of the curriculum in facilitating the optimal development of students' potential.